Narrowband light detection via internal quantum efficiency manipulation of organic photodiodes - Ardalan Armin (Nature Communications, 2015)
Spectrally selective, narrowband light detection is vital for full-color and Near Infrared (NIR) imaging, intelligent monitoring and machine vision. This is not possible using traditional broadband absorbing inorganic semiconductors without input filtering, nor narrowband absorbing organic semiconductors particularly for the red and NIR. We demonstrate the first sub-100nm FWHM (Full-Width-at-Half-Maximum) visible-blind red and NIR photodetectors with state-of-the-art performance across critical response metrics. These devices are based upon organic photodiodes with optically thick junctions. Paradoxically, we use broadband absorbing organic semiconductors and utilize the electro-optical properties of the junction to create the narrowest band photoresponses yet demonstrated. In this context, these photodiodes outperfrom the encumbent technology (input filtered inorganic semiconductor diodes) and emerging technologies such as narrow absorber organic semiconductors or quantum nanocrystals. The design concept allows for response tuning and is generic for other spectral window. Furthermore, it is materials agnostic and applicable to disordered semiconductors such as perovskites.